Comparison of laparoscopic versus robot-assisted versus transanal total mesorectal excision surgery for rectal cancer: a retrospective propensity score-matched cohort study of short-term outcomes. Issue 11 (9th August 2021) - Hol, J C; Burghgraef, T A; Rutgers, M L W; Crolla, R M P H; van Geloven, N A W; Hompes, R; Leijtens, J W A; Polat, F; Pronk, A; Smits, A B; Tuynman, J B; Verdaasdonk, E G G; et al.
Abstract: Background: Laparoscopic total mesorectal excision (TME) surgery for rectal cancer has important technical limitations. Robot-assisted and transanal TME (TaTME) may overcome these limitations, potentially leading to lower conversion rates and reduced morbidity. However, comparative data between the three approaches are lacking. The aim of this study was to compare short-term outcomes for laparoscopic TME, robot-assisted TME and TaTME in expert centres. Methods: Patients undergoing rectal cancer surgery between 2015 and 2017 in expert centres for laparoscopic, robot-assisted or TaTME were included. Outcomes for TME surgery performed by the specialized technique in the expert centres were compared after propensity score matching. The primary outcome was conversion rate. Secondary outcomes were morbidity and pathological outcomes. Results: A total of 1078 patients were included. In rectal cancer surgery in general, the overall rate of primary anastomosis was 39.4, 61.9 and 61.9 per cent in laparoscopic, robot-assisted and TaTME centres respectively ( P  < 0.001). For specialized techniques in expert centres excluding abdominoperineal resection (APR), the rate of primary anastomosis was 66.7 per cent in laparoscopic, 89.8 per cent in robot-assisted and 84.3 per cent in TaTME ( P  < 0.001). Conversion rates were 3.7, 4.6 and 1.9 per cent in laparoscopic, robot-assisted and TaTME respectively ( P  = 0.134). The number of incomplete specimens, circumferential resection margin involvement rate and morbidity rates did not differ. Conclusion: In the minimally invasive treatment of rectal cancer more primary anastomoses are created in robotic and TaTME expert centres. Lay Summary: The results of this study showed similar and acceptable short-term results for laparoscopic, robot-assisted and transanal total mesorectal excision performed in expert centres. In centres with robot-assisted or transanal technique, more primary anastomoses were made. Abstract : The results of this study showed similar and acceptable short-term results for laparoscopic, robot-assisted and transanal total mesorectal excision performed in expert centres. In centres with robot-assisted or transanal technique, more primary anastomoses were made.